2005
DOI: 10.1002/cbic.200400334
|View full text |Cite
|
Sign up to set email alerts
|

Smart Polyion Complex Micelles for Targeted Intracellular Delivery of PEGylated Antisense Oligonucleotides Containing Acid‐Labile Linkages

Abstract: A novel pH-sensitive and targetable antisense ODN delivery system based on multimolecular assembly into polyion complex (PIC) micelles of poly(L-lysine) (PLL) and a lactosylated poly(ethylene glycol)-antisense ODN conjugate (Lac-PEG-ODN) containing an acid-labile linkage (beta-propionate) between the PEG and ODN segments has been developed. The PIC micelles thus prepared had clustered lactose moieties on their peripheries and achieved a significant antisense effect against luciferase gene expression in HuH-7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 41 publications
1
82
0
5
Order By: Relevance
“…Intracellular environments with a low pH in endosomes/lysosomes are employed as triggers of PEG cleavage. [97][98][99][100][101][102] Szoka and colleagues constructed pHsensitive PEG lipids containing an orthoester linkage, and a transfection experiment showed greater luciferase expression of pH-sensitive lipoplexes as compared with stable PEGylated ones. 97) In addition to the pH gradient, an intracellular reducing environment and enzymes are considered alternative stimulating triggers.…”
Section: -28)mentioning
confidence: 99%
“…Intracellular environments with a low pH in endosomes/lysosomes are employed as triggers of PEG cleavage. [97][98][99][100][101][102] Szoka and colleagues constructed pHsensitive PEG lipids containing an orthoester linkage, and a transfection experiment showed greater luciferase expression of pH-sensitive lipoplexes as compared with stable PEGylated ones. 97) In addition to the pH gradient, an intracellular reducing environment and enzymes are considered alternative stimulating triggers.…”
Section: -28)mentioning
confidence: 99%
“…[13][14][15] Polymer based nanoparticles composed of pH-sensitive linkages have been also reported. [16][17][18] Walker et al demonstrated successful gene delivery using pH-sensitive polyplexes with pH-labile hydrazone linkages between the PEG and polycation for in vitro and in vivo use.…”
Section: Activation In Response To Endogenous/internal Stimulimentioning
confidence: 99%
“…33, 38 The micelle systems containing PEI were designed in such a fashion that the ODN can be released by hydrolysis from the PEO segment. Moreover, the stability of the DNA-b-PEO within the polyion complex micelles against deoxyribonuclease (DNase I) was demonstrated.…”
Section: Dbcs As a New Gene Delivery Systemmentioning
confidence: 99%